Apoptotic cell therapy for cytokine storm associated with acute severe sepsis - Karbian, Netanel (Cell Death Dis, 2020)
Sepsis has no proven pharmacologic treatment other than appropriate antibiotic agents, fluids, vasopressors as needed, and possibly corticosteroids. It is generally initiated mainly by the simultaneous recognition by various components of the innate immune system of either pathogen-associated molecular patterns (PAMPs) or damage-associated molecular patterns (DAMPs). In the current study, we employed the murine cecal ligation and puncture (CLP) model for sepsis to evaluate the effect of post-CLP infusion of apoptotic cells (Allocetra-OTS) on a CLP severe sepsis model. Cardiovascular evaluation, acute kidney injury (AKI), acute liver injury (ALI), and hematological and metabolic function were evaluated. Cytokine and chemokine profiles were measured by Multiplex ELISA and mitochondrial function, and glycolysis by Seahorse. The Murine Sepsis Score (MSS) was used for disease severity definition. CLP mice had low blood pressure, poor cardiac output, and lung dysfunction, as well as AKI, ALI, and thrombocytopenia, which correlated with the MSS and corresponded to a cytokine/chemokine storm. Apoptotic cell administration markedly improved the cytokine and chemokine storm and restored the impaired mitochondrial and glycolytic function in white blood cells leading to increased survival, from 6 to 60% (P < 0.0001), together with a significant improvement in organ dysfunction. We conclude that the deleterious immune response in CLP-induced sepsis can be successfully modified by apoptotic cell infusion.